Pengembangan Pariwisata terhadap Pendapatan Masyarakat di Kota Sabang pada masa New Normal - Muhammad Yusra; Dy Ilham Satria; Ridha Firdaus; Mauidhatul Jannah (Jurnal Akuntansi dan Keuangan, 2023)
The tourism sector of Sabang City has so much potential, such as the Rubiah Island marine park, Iboih Beach, Gapang Beach, Anai Itam Beach, and others. For this reason, the local government of Sabang City with such rich potential for tourism objects is required to develop the tourism sector through careful and thorough planning, which is expected to have a very significant impact in order to increase revenue.The purpose of this study is to analyze the strategy of developing tourism objects in Sabang City in increasing income, the factors that become obstacles in the implementation of tourism object development strategies, and the efforts made in overcoming obstacles in the implementation of tourism object development strategies in Sabang City. Data collection was carried out through direct observation in the field, guided interviews, questionnaires, documentation and literature studies. With research stages which include; data observation, determining the main problem, activity objectives, literature study, data collection, data processing, analysis of results and evaluation, application of research results.The research results obtained: (1) The tourism development strategy implemented has experienced significant developments to increase people's income, but is not optimal, (2) The main inhibiting factors in the tourism development strategy are the limited budget for tourism, and promotion that has not been maximized, ( 3) Efforts that have been made by the government are making events, promoting Sabang City tourism, forming tourism-aware community groups, and Tourism Villages.